The Economic Value of Baluran National Park Natural Resources Utilization by Wonorejo Villagers, Situbondo District East Java - Elsha Cyntiana Dewi; Tutut Sunarminto; Harnios Arief (Media Konservasi, 2017)
Baluran National Park ( TNB ) managed not only to preserve the ecological function but also be able to confers a benefit for the people around them. One of the benefits felt by the communities from the existence of TNB is the economic value from natural resources utilization. This research aimed to calculate economic value and community dependency toward TNB natural resources also legal aspect of the utilization. This research conducted in march 2016 in Wonorejo Village. Data collection carried out by interviews, focus group discussions (FGD), field observation and literature study. The research results show that economic value of natural resources utilization by society worth of 973.799.746,00. Wonorejo sociesty having high dependency toward TNB natural resources. Natural resources withdrawal by the society is not only conducted in Traditional Zone of TNB but also reach Rimba Zone even Core Zone. Rimba Zone is the highest interaction area between society and natural resources of Baluran National Park Keywords: economic value, natural resources, wonorejo society,  zoning